2021
DOI: 10.25259/ijdvl_293_19
|View full text |Cite
|
Sign up to set email alerts
|

A case of disseminated subcutaneous phaeohyphomycosis caused by Exserohilum rostratum with CARD9 mutation

Abstract: Phaeohypomycosis is a rare cutaneous and subcutaneous fungal infection caused by dematiaceous fungi. They have a widespread global distribution occasionally affecting humans. A 26-year-old woman presented with multiple skin lesions over her face and extremities for last 7 years, unresponsive to systemic amphotericin B and itraconazole. Further investigations revealed CARD9 mutation and phaeohyphomycosis caused by the pigmented fungus Exserohilum rosatratum. Lesions subsequently improved with oral flucytosine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Nearly 35 years later, the first evidence to support his hypothesis was confirmed with the identification of AR CARD9 deficiency in four patients with pheohyphomycosis due to P. verrucosa [ 447 ]. This inborn error of immunity has since been identified in pheohyphomycosis due to Exophiala [ 448 , 449 , 450 , 451 ], other Phialophora species [ 452 ], Aureobasidium [ 453 ], Alternaria [ 454 , 455 ], and Exserohilum [ 456 ], as well as more esoteric dematiaceous fungi, including Pallidocercospora crystallina , Ochroconis musae, and Corynespora cassiicola [ 449 , 457 , 458 , 459 ]. Intriguingly, disseminated infection with C. cassiicola (with extension into the CNS) has also been reported in a patient with compound heterozygous mutations in CLEC7A (encoding Dectin-1, which is a fungal pattern recognition receptor that signals through CARD9) [ 460 ].…”
Section: Pheohyphomycosis (Dematiaceous Fungi)mentioning
confidence: 99%
“…Nearly 35 years later, the first evidence to support his hypothesis was confirmed with the identification of AR CARD9 deficiency in four patients with pheohyphomycosis due to P. verrucosa [ 447 ]. This inborn error of immunity has since been identified in pheohyphomycosis due to Exophiala [ 448 , 449 , 450 , 451 ], other Phialophora species [ 452 ], Aureobasidium [ 453 ], Alternaria [ 454 , 455 ], and Exserohilum [ 456 ], as well as more esoteric dematiaceous fungi, including Pallidocercospora crystallina , Ochroconis musae, and Corynespora cassiicola [ 449 , 457 , 458 , 459 ]. Intriguingly, disseminated infection with C. cassiicola (with extension into the CNS) has also been reported in a patient with compound heterozygous mutations in CLEC7A (encoding Dectin-1, which is a fungal pattern recognition receptor that signals through CARD9) [ 460 ].…”
Section: Pheohyphomycosis (Dematiaceous Fungi)mentioning
confidence: 99%
“…3 Recent studies have revealed that inherited CARD9 deficiency increases the risk of superficial and invasive fungal diseases caused by various fungi, including severe or disseminated phaeohyphomycosis. 4 In the past 20 years, 18 cases of CARD9-deficient phaeohyphomycosis have been identified worldwide, [5][6][7][8][9][10][11][12][13][14][15] nine of which were from our clinical centre. [12][13][14][15] According to our previous studies, peripheral blood mononuclear cells (PBMCs) obtained from CARD9-deficient patients exhibited a selective impairment of proinflammatory cytokine production and adaptive immune responses upon specific simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, 18 cases of CARD9‐deficient phaeohyphomycosis have been identified worldwide, 5‐15 nine of which were from our clinical centre 12‐15 . According to our previous studies, peripheral blood mononuclear cells (PBMCs) obtained from CARD9‐deficient patients exhibited a selective impairment of proinflammatory cytokine production and adaptive immune responses upon specific simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, 18 cases of CARD9-de cient phaeohyphomycosis have been identi ed worldwide [5][6][7][8][9][10][11][12][13][14][15], nine of which have been from our clinical center [12][13][14][15]. According to our previous studies, peripheral blood mononuclear cells (PBMCs) obtained from CARD9-de cient patients exhibited a selective impairment of proin ammatory cytokine production and adaptive immune responses upon speci c simulations.…”
Section: Introductionmentioning
confidence: 99%